A Survey on Wireless Charging of Electric Vehicles - Niranjan D N; Tilak Naidu R; Vijay Aditya; Dr. Sunitha S V (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Wireless charging enables efficient power transfer through electromagnetic induction between transmitter and receiver coils, eliminating the need for physical connectors and enhancing safety and convenience. In this proposed system, solar panels serve as the primary energy source, converting sunlight into electrical energy via the photoelectric effect in silicon cells and using it to wirelessly charge batteries through a clean, contactless process. The integration of Wireless Power Transfer (WPT) with renewable solar energy supports the development of eco-friendly charging infrastructure, particularly for electric vehicles (EVs), reducing dependency on fossil fuels and minimizing environmental pollution. The system incorporates Internet of Things (IoT) technology to enable real-time monitoring of charging parameters, energy flow, and automation of billing and control processes. Recent advancements in WPT coil design, compensation networks, and power electronics have improved energy efficiency and alignment tolerance, making wireless EV charging more practical for dynamic and stationary applications. Overall, this work presents a smart, solar-powered, IoT- enabled wireless charging solution aimed at achieving sustainable, contactless, and autonomous electric vehicle charging, contributing to the vision of cleaner mobility and future smart transportation systems.